2016
DOI: 10.3892/ol.2016.4074
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing antipsychotics as glioblastoma therapeutics: Potentials and challenges

Abstract: Abstract. Glioblastoma multiforme (GBM) is the most common and most lethal primary brain tumor, with tragically little therapeutic progress over the last 30 years. Surgery provides a modest benefit, and GBM cells are resistant to radiation and chemotherapy. Despite significant development of the molecularly targeting strategies, the clinical outcome of GBM patients remains dismal. The challenges inherent in developing effective GBM treatments have become increasingly clear, and include resistance to standard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 104 publications
0
49
0
Order By: Relevance
“…These include a small increased risk of cardiac arrhythmia with long term use, and extrapyramidal toxicity that can be potentially permanent. Notably, several PTH antipsychotics were reported to have significant antitumoral effects with several cancer cell lines and their repurposing has been proposed even though their cellular targets have not been identified, and they were generally assumed to work largely through inhibition of dopamine receptors . Interestingly, an analysis from five independent studies of PCa incidence in individuals with schizophrenia revealed a significant decrease in Standardized Incidence Ratio ranging from 0.49 to 0.76 (95% CI) .…”
Section: Discussionmentioning
confidence: 99%
“…These include a small increased risk of cardiac arrhythmia with long term use, and extrapyramidal toxicity that can be potentially permanent. Notably, several PTH antipsychotics were reported to have significant antitumoral effects with several cancer cell lines and their repurposing has been proposed even though their cellular targets have not been identified, and they were generally assumed to work largely through inhibition of dopamine receptors . Interestingly, an analysis from five independent studies of PCa incidence in individuals with schizophrenia revealed a significant decrease in Standardized Incidence Ratio ranging from 0.49 to 0.76 (95% CI) .…”
Section: Discussionmentioning
confidence: 99%
“…Repositioning of existing drugs has drawn attention as a promising drug discovery approach for GSC-targeted therapy. Among potential drug candidates for repurposing antipsychotics, mood stabilizers, anticonvulsants, and small molecules that can easily pass through BBB may be useful for treating GBM [ 25 ]. A number of antipsychotic drugs, mood stabilizers, and antiepileptic drugs have shown antitumor effects [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These obstacles call for tailored therapeutic strategies to counter tumor heterogeneity and overcome roadblocks in delivery. RNAi targeting drivers of tumorigenesis shows strong potential to supplement the development of traditional small-molecule pharmaceutics (6). However, delivery remains a key obstacle for efficient RNAi against tumor drivers (5,7,8).…”
mentioning
confidence: 99%